Decentralized governance for development: a combined practice note on decentralization, local governance and urban / rural development - Programa de las Naciones Unidas para el Desarrollo Autoría 25082 ([S.l.] , [S.l.] : Programa de las Naciones Unidas para el Desarrollo, 2004)
Digital